2017
DOI: 10.18203/2349-3933.ijam20175169
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid levels in the diabetic and non diabetic patients: a study in a tertiary care hospital

Abstract: Background: The incidence of coronary artery diseases is 3 to 5 times higher in both male and female diabetic patients compared to general population. Individuals with diabetes may have several forms of dyslipidemia leading to additive cardiovascular risk of hyperglycemia. This study was therefore conducted to identify the levels of lipidemia in the diabetic patients in our area. Methods: This study was conducted on 100 diabetic and 100 healthy patients, with 50 patients were males and 50 were females in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…An elevation in the activities of LDL-C (17.29% increase) and VLDL-C (30% increase) was observed in the present study which was in agreement with other previous studies [22,27,28].…”
Section: Discussionsupporting
confidence: 94%
“…An elevation in the activities of LDL-C (17.29% increase) and VLDL-C (30% increase) was observed in the present study which was in agreement with other previous studies [22,27,28].…”
Section: Discussionsupporting
confidence: 94%
“…Reports also showed that BGN contains mono and polyunsaturated fatty acid, which helps to decrease level of LDL-C and increase levels of high density lipoprotein (HDL-C) in blood [54]. The levels of TCH and LDL-C in diabetic rats blood obtained in this study were within the acceptable level (200-239 mg/dl) and (100-159 mg/dl) respectively [55].…”
Section: Lipids Of Diabetic Rats Fed With Finger Millet Bambara Groun...supporting
confidence: 60%
“…The non-diabetic rats group (Negative-Control) had the highest TGL value of 168.87 mg/dl (Table 3). Veeramalla and Madas, [55] also observed higher TGL levels in nondiabetic patients. Low TGL levels of the diabetic rat groups could be attributed to weight loss or possibly genetic [55].…”
Section: Lipids Of Diabetic Rats Fed With Finger Millet Bambara Groun...mentioning
confidence: 78%
See 1 more Smart Citation